PENGARUH STRUKTUR MODAL, PERTUMBUHAN LABA, KEPEMILIKAN INSTITUSIONAL DAN LIKUIDITAS TERHADAP KUALITAS LABA (Studi pada Perusahaan Pertambangan yang terdaftar di Bursa Efek Indonesia periode 2012-2016) - Dita Setya Ningrum, 14.05.52.0010; Suwarti, Titiek (Students' Journal of Accounting and Banking, 2018)
Thepurpose of this study is to examines and analyses the effect of capital structure, profit growth,andliquidity to earning quality. This research was conducted at base industry and chemical company listed on Indonesia Stock Exchange (BEI). The sampling method used in this study is purposive sampling with observation period 2012 to 2016 the number of samples obtained as much as 28. The influence between variables is discribed by using multiple regression analysis with SPSS 21 program. The type of data used is secondary data. The results showed that the institutional ownership positive affecting the earning quality. And the profit growth and liquiditynegative significantly affect the earning quality. While the capital structure do not significantly affect the earning quality. Keywords : Capital structure, profit growth, liquidity and earning quality